2016
DOI: 10.3892/mmr.2016.5256
|View full text |Cite
|
Sign up to set email alerts
|

Expression and function of microRNA-497 in human osteosarcoma

Abstract: The expression and function of microRNA-497 (miR-497) has previously been reported in various types of human cancer; however, miR-497 has not previously been investigated in human osteosarcoma (OS). In the present study, the expression levels of miR‑497 were analyzed by reverse transcription‑quantitative polymerase chain reaction (RT‑qPCR) in OS tissues and cell lines. In addition, post-transfection with miR‑497, RT‑qPCR, cell proliferation, migration and invasion assays, western blot analysis, and luciferase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 48 publications
(49 reference statements)
0
8
0
Order By: Relevance
“…Therefore, tumor-suppressing miRNAs are usually downregulated, whereas oncogenic miRNAs tend to be overexpressed in cancer (12). Previous studies have reported the deregulation of miRNA expression in OS (13)(14)(15), and miRNA expression has been correlated with tumor stage and aggressiveness (16). Therefore, it is critical to understand the roles of miRNAs in cancer development and progression, and explore their potential as novel therapeutic targets for the treatment of patients with cancer.…”
Section: Upregulation Of Microrna-25-3p Inhibits Proliferation Migramentioning
confidence: 99%
“…Therefore, tumor-suppressing miRNAs are usually downregulated, whereas oncogenic miRNAs tend to be overexpressed in cancer (12). Previous studies have reported the deregulation of miRNA expression in OS (13)(14)(15), and miRNA expression has been correlated with tumor stage and aggressiveness (16). Therefore, it is critical to understand the roles of miRNAs in cancer development and progression, and explore their potential as novel therapeutic targets for the treatment of patients with cancer.…”
Section: Upregulation Of Microrna-25-3p Inhibits Proliferation Migramentioning
confidence: 99%
“…Low miR-497 expression may be a predictor of poor prognosis. Furthermore, miR-497 is expressed at low levels in non-small cell lung cancer ( 35 ), prostate cancer ( 36 ), pancreatic cancer ( 37 ), ovarian cancer ( 38 ), bladder cancer ( 39 ) and osteosarcoma ( 40 ). These findings suggested that miR-497 is frequently lowly expressed in human cancer and could be a therapeutic marker for its diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…IGF-1R, a tyrosine kinase receptor, contains two extracellular α subunits with a ligand-binding site, two transmembrane β subunits and intracellular tyrosine kinase activity (29). It has previously been demonstrated that IGF-1R is involved in IGF-I and IGF-II signaling, and therefore regulates cell proliferation, cell cycle, apoptosis, metastasis, survival and differentiation (30)(31)(32)(33).…”
Section: Discussionmentioning
confidence: 99%